SURFACE STRENGTH OF NOVIKOV CONVEXO-CONCAVE GEARS - Michał BATSCH (Scientific Journal of Silesian University of Technology. Series Transport)
Article presents the algorithm for obtaining maximum surface stresses for Novikov gears. Described surface strength calculation method is based on Hertz theory of two bodies being in point contact. What’s more the influence of gear position errors on maximum contact stresses has been presented. Also the comparison of Hertz stresses for Novikov and involute gears has been made.